Aplikasi Sari Daun Kelor Sebagai Zat Pengatur Tumbuh Organik Terhadap Pertumbuhan Dan Kadar Klorofil Tanaman Kedelai (Glycine max (L.) Merr.) - Fauziah Laily Amriyanti; Purity Sabila Ajiningrum (FMIPA : Universitas PGRI Adi Buana, 2019)
Soybean as a protein sources can fill the needs of public’s food increasily but the production in this country is still low. Therefore, cultivation efforts are needed to improve the growth and development of soybean plants. Some factors that are sufficient to influence the plant growth process are nutrient supply, water availability, sunlight, air temperature, oxygen and growth regulators. Plant Growth Regulator (PGR) that can be used is moringa leaves as a source of cytokinins. Cytokinin serves stimulating cell division, postpone the process of aging plants, and spur growth budding. This study aims to determine the effect of giving plant growth organic made by moringa leaves with 2 control, which are negative control (0%) and positive control (cytokinin synthetic solution) and 3 treatment at concentration of P1 (10%), P2 (20%), P3 (30%) to increase the growth soy plants and to know the concentration optimally of any treatment given. This research using the completely randomized design (CRD) with 5 treatment and 5 replicate. The results were analyzed using the ANOVA test followed by the LSD/BNT test and the Duncan test. The results showed that the application of organic PGR made from Moringa leaves had a significant effect (P <0.05) on growth (plant height and number of leaves) and chlorophyll content in soybean plants had optimal concentrations at 30% concentration. Keywords: moringa leaves, cytokinin, soybean plants, plant growth regulator.